Effect of Thoracic Hyper-Kyphosis Posture on Upper Extremity Function of Female Students - Mohammad Karimizadeh Ardakani; Zahra Soroush Fard; Fatemeh Amirizadeh; Homa Naderifar (Journal of Rehabilitation Sciences and Research, 2022)
Background: Thoracic hyper-kyphosis is one of the most common posturaldisorders of the spinal column. Decreased strength of spinal extensor musclesand range of motion of joints such as the shoulder is associated with hyperkyphosis,which can affect the physical function and life of an individual. The fpresent study aimed to investigate the effect of thoracic hyper-kyphosis on upperextremity function among female students.Methods: The current cross-sectional study included a population consistingof 226 female students aged 13-18 years old divided into two groups: 113participants with normal and 113 with abnormal thoracic hyper-kyphosis. Thekyphosis angle was measured using a flexible ruler, and the Y test, Davis test, anddisabilities of the arm, shoulder, and hand (DASH) questionnaire were used tomeasure upper extremity function. Independent t-test and Pearson’s correlationwere employed for data analysis.Results: The Davis, Y, and DASH test results showed a significant differencein upper extremity function between subjects with and those without thoracichyper-kyphosis (P<0.05), with the abnormal thoracic hyper-kyphosis groupshowing poorer function than the normal group. The results also demonstrateda significant relationship between the kyphosis angle and the Davis, Y, andDASH tests (P<0.05).Conclusion: Overall, kyphosis abnormality was found to lead to weak upperextremity function, and an inverse relationship was observed between thekyphosis angle and the Davis test and Y balance test. Moreover, a directrelationship was found between the kyphosis angle and DASH test.